2017
DOI: 10.1021/acs.jpcb.6b09147
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Chain Propagation Rate Constants of Polymerization Reactions in Aqueous NIPAM/BIS and VCL/BIS Systems

Abstract: Microgels have a wide range of possible applications and are therefore studied with increasing interest. Nonetheless, the microgel synthesis process and some of the resulting properties of the microgels, such as the cross-linker distribution within the microgels, are not yet fully understood. An in-depth understanding of the synthesis process is crucial for designing tailored microgels with desired properties. In this work, rate constants and reaction enthalpies of chain propagation reactions in aqueous N-isop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 56 publications
5
83
0
Order By: Relevance
“…This behavior is in accordance with off‐line kinetic studies using quantitative 1 H‐NMR spectroscopy of VCL and NIPAM copolymerization from Balaceanu et al From samples taken during reaction at 70 °C, they identified a PVCL:PNIPAM composition of 0.4–0.55 mol mol −1 before 10 min of reaction time and a composition of 0.9–1.2 mol mol −1 after, which supports faster NIPAM than VCL conversion . A recent simulation of chain propagation rate constants calculated higher rate constants for NIPAM than for VCL . Hence, slower conversion of NIPAM in homopolymerization is due to rate limiting effects, which are different from the kinetics of chain reaction.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…This behavior is in accordance with off‐line kinetic studies using quantitative 1 H‐NMR spectroscopy of VCL and NIPAM copolymerization from Balaceanu et al From samples taken during reaction at 70 °C, they identified a PVCL:PNIPAM composition of 0.4–0.55 mol mol −1 before 10 min of reaction time and a composition of 0.9–1.2 mol mol −1 after, which supports faster NIPAM than VCL conversion . A recent simulation of chain propagation rate constants calculated higher rate constants for NIPAM than for VCL . Hence, slower conversion of NIPAM in homopolymerization is due to rate limiting effects, which are different from the kinetics of chain reaction.…”
Section: Resultssupporting
confidence: 85%
“…Copolymerization is substantially more complex to control than homopolymerization due to cross-reactions between both monomers. [15] In view of the functional applications mentioned above, accurate control of conversion of each individual monomer is crucial, which requires accurate knowledge of the conversion of individual monomers. Raman spectroscopy was found to be applicable to monitor microgel syntheses since the monomer CC bonds are Raman active.…”
Section: Doi: 101002/mren201700067mentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is the barrier in Gibbs free energy that the reaction must overcome to achieve product formation. This barrier can be predicted from ideal gas and solvation properties , .…”
Section: Methodsmentioning
confidence: 99%